2019
DOI: 10.1590/1678-5150-pvb-5790
|View full text |Cite
|
Sign up to set email alerts
|

Use of infrared thermography in Quarter Horse submitted to team roping

Abstract: This study aimed to verify whether the body and local temperatures change after high-intensity, short-duration exercise (team roping) and whether different pieces of training influence these changes. To this end, twelve animals, males and females, aged 3-6 years, with an average weight of 450 kg, were used. The horses were divided into two groups: regular training (RTG) and sporadic training (STG). The surface temperatures were assessed using a specific thermal camera. Temperatures of the ocular, thoracolumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, our results showed a significant statistical decrease in IOP after exercise, in contrast to other findings [ 3 , 23 ]. No statistical effect was found on IOP between the a.m. and p.m. hours, suggesting that IOP is not affected by changes in the thermoregulation system which is activated between morning and afternoon as the body temperature increases after exercise [ 3 , 38 ]. The decrease in IOP observed after physical exercise may be associated with cardiovascular, systemic and hemodynamic adaptations intra- and post-exercise (such as changes in the heart rate, elevated systolic and diastolic blood pressure), which may be necessary to ensure the proper supply of oxygen and blood-transported substrates to activate the muscular system during exercise, along with the release of metabolites [ 22 , 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results showed a significant statistical decrease in IOP after exercise, in contrast to other findings [ 3 , 23 ]. No statistical effect was found on IOP between the a.m. and p.m. hours, suggesting that IOP is not affected by changes in the thermoregulation system which is activated between morning and afternoon as the body temperature increases after exercise [ 3 , 38 ]. The decrease in IOP observed after physical exercise may be associated with cardiovascular, systemic and hemodynamic adaptations intra- and post-exercise (such as changes in the heart rate, elevated systolic and diastolic blood pressure), which may be necessary to ensure the proper supply of oxygen and blood-transported substrates to activate the muscular system during exercise, along with the release of metabolites [ 22 , 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors reported significant temperature increases in hindlimb muscle surface right after different exercises (Simon et al, 2006;Yarnell et al, 2014;Gerardi, et al, 2019), others could not detect forelimb muscle temperature variation in Quarter horses (Oliveira et al, 2018).…”
mentioning
confidence: 94%
“…In addition, IRT could be used during training programs to ensure muscles are working symmetrically and indicate which terrains or training programs cause an increase in muscle workload (Yarnell et al, 2014;Gerardi, et al, 2019).…”
mentioning
confidence: 99%
“…Segundo a Associação Brasileira de Vaquejada -ABVAQ, o mercado vinculado a atividade era de aproximadamente R$ 600 milhões de reais por ano em 2017, o que justifica os altos investimentos feitos na manutenção desses animais em bom estado clínico em busca da garantia de que estarão aptos a competir com seu máximo rendimento atlético (GERARDI et al, 2019).…”
Section: Introductionunclassified